Nurses' Empowerment in Self-Care Education to Stroke Patients: An Action Research Study - Zahra Aslani; Nasrollah Alimohammadi; Fariba Taleghani; Parvaneh Khorasani (Shiraz University of Medical Sciences, 2016)
Background: Self-care needs are major problems among stroke patients. Nurses can support them through interventions such as education, a change in their attitude and emphasis on their remaining abilities. However, research has shown some weak points in the quality of care given to these patients. So the aim of this study was to improve the nurses' practice in self-care education to stroke patients. Methods: This is a participatory action research, conducted in internal neurology ward of Al-Zahra hospital in Isfahan, Iran during 2013-2014 in five stages of diagnosis, planning, action, reflection and evaluation. Participants comprised 27 nursing personnel including staff nurses, matrons, educational supervisors and the staff in charge of Nurse Educators' Al_Zahra Role Expansion Action Research (NEAREAR) project. In the evaluation stage, data were collected from five personal interviews and two focus group discussions and analyzed by qualitative content analysis. Results: The findings of evaluation phase showed that during action research, approaching the nurses' empowerment in self-care education to stroke patients has been set in motion. The nursing practice improvement, knowledge based practice, nurses' attitude change, ability to respond against routinization, and motivation promotion emphasize the success of change process. Facilitators and barriers of educating patients are acknowledged by the participants as a factor influencing the continuation of change. Conclusions: The lack of nurses' educating performance skills was overcome using action research and changes were made to improve the performance of nurses.